2017
DOI: 10.1007/s10461-017-1705-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associations of Psychological Distress, HIV Infection and HIV Care Service Utilization in East Zimbabwe

Abstract: The correlation between mental health and sexual risk behaviours for HIV infection remains largely unknown in low and middle income settings. The present study determined the prevalence of psychological distress (PD) in a sub-Saharan African population with a generalized HIV epidemic, and investigated associations with HIV acquisition risk and uptake of HIV services using data from a cross-sectional survey of 13,252 adults. PD was measured using the Shona Symptom Questionnaire. Logistic regression was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
3
17
1
1
Order By: Relevance
“…Poor mental health, in the form of greater psychological distress, is associated with lower ART uptake in east Zimbabwe. 29 As in many previous studies, 37 we found that psychological distress was more common in sex workers but we did not find this was an important factor mediating uptake. FSWs in this study also reported higher levels of stigma linked to HIV than NSWs; however, unlike studies elsewhere in Zimbabwe, 38 we did not find stigma to be a significant deterrent to accessing healthcare.…”
Section: Discussioncontrasting
confidence: 49%
“…Poor mental health, in the form of greater psychological distress, is associated with lower ART uptake in east Zimbabwe. 29 As in many previous studies, 37 we found that psychological distress was more common in sex workers but we did not find this was an important factor mediating uptake. FSWs in this study also reported higher levels of stigma linked to HIV than NSWs; however, unlike studies elsewhere in Zimbabwe, 38 we did not find stigma to be a significant deterrent to accessing healthcare.…”
Section: Discussioncontrasting
confidence: 49%
“…Nevertheless, there were indications that CTs in Manicaland shifted distributions of reported symptoms of psychological distress and a qualitative study of the Trial found that children and guardians in households receiving CTs reported reduced levels of stress and anxiety [ 61 ]. A previous analysis of the study population found links between psychological distress and potentially risky sexual behaviour [ 46 ], so improved mental health may have contributed to reduced recent sexual activity, although reverse causality is possible. Similarly, the Kenyan CT evaluation found a mediating role of mental health [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes, analysed for their potential in mediating effects on sexual behaviour (Fig. 3 ), included school enrolment [ 44 , 45 ], psychological distress [ 46 ], and consumption of alcohol, cigarettes, and drugs. See Additional file 2 (section 1) for information on data for measures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…People living with HIV (PLHIV) show elevated rates of depression, anxiety and trauma [ 12 14 ], which may be due to HIV-related stigma [ 15 , 16 ], the direct disease burden, or the impact of an HIV diagnosis on quality of life and relationships. People with mental health challenges are also at greater risk of HIV exposure and acquisition [ 17 19 ]. A recent survey of adults in Zimbabwe found that psychological distress was associated with increased sexual risk behaviour among seronegative individuals, and with reduced adherence to treatment for PLHIV [ 17 ].…”
Section: Introductionmentioning
confidence: 99%